PENGARUH PARKIR PADA JALAN TERHADAP KINERJA RUAS JALAN ABUL HASAN DI KOTA SAMARINDA - JUNAIDI, JUNA (KURVA S JURNAL MAHASISWA, 2014)
Junaidi , technique faculty, study program civil faculty, 17 august 1945 Samarinda University. Research tittle “ Park effect at Road body about procedure Abul Hasan space road in Samarinda city “. This thesis under guidance Ir. Yohanes Nono Juwono MT as counselor I and Sahrullah , ST, MT as counselor II.Traffic jam which caused by shop matters activity indirect have impact to transportation problem many of vehicle which parking, but less of suitable parking area so still found park at border road, so often caused traffic jam in this road.The purpose of this thesis writing is to know par k effect level at Abul Hasan road body in Samarinda city. Substance of this thesis as condition graduate BA Degree in 17 August 1945 University in Samarinda. As information substance for next researcher especially which related with traffic jam and park density at Abul Hasan road body in Samarinda City.From data of result research based on calculation by park existence in road body in this space influence vehicle speed. It seen from speed descent which should more than 45 km/hour (<45km /hour) become 17.234 km/hour .Based on research result hoped at busy hours reduce beside obstacle, because with high beside obstacle will reduce vehicle speed and make density increase so occur adjournment or jamming also reduce road capacity and servicing level in Abul Hasan road space. Expected any park facility that large enough so that nothing vehicle that park in road body caused school and shop matter activity.